Evaluation of Medication Errors in Transcribing and Dispensing Processes of Outpatient E-Prescriptions at Persahabatan General Hospital - Khairani, Sondang; Nurhayati, Fitri; Kurnia, Mala; Manninda, Reise; Ariani, Lusiana (Sciences of Pharmacy, 2025)
Persahabatan General Hospital provides a variety of healthcare services, including outpatient care. Medication errors are errors in the prescribing, dispensing, and administration process that can be considered risk factors for patients. This study aims to evaluate medication errors in the transcription and dispensing phases of outpatient e-prescriptions at Persahabatan General Hospital during the period January - February 2024. This research is a descriptive observational study with a cross-sectional design. Data were collected through prospective observation and analyzed descriptively to determine the percentage of medication errors. Of the 363 e-prescriptions observed, the results showed no errors in the transcribing phase. However, in the dispensing phase, there were 50 (6.07%) incidents of incorrect preparing quantity of medicine, 8 (0.97%) incidents of incorrect medicine medical equipment, and 7 (0.85%) incidents of incorrect dosage. These findings suggest that although the implementation of e-prescribing is effective in reducing errors at the transcription phase, special attention must be paid to the dispensing phase to reduce the number of errors. There is a correlation between polypharmacy and medication errors in the dispensing phase, p-value <0.001. All of these errors are resolved before the medication is administered to the patient.